2019
DOI: 10.1186/s13054-019-2562-y
|View full text |Cite|
|
Sign up to set email alerts
|

The association between premorbid beta blocker exposure and mortality in sepsis—a systematic review

Abstract: Background The effect of premorbid β-blocker exposure on clinical outcomes in patients with sepsis is not well characterized. We aimed to examine the association between premorbid β-blocker exposure and mortality in sepsis. Methods EMBase, MEDLINE, and Cochrane databases were searched for all studies of premorbid β-blocker and sepsis. The search was last updated on 22 June 2019. Two reviewers independently assessed, selected, and abstracted data from studies reporting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 37 publications
2
45
0
1
Order By: Relevance
“… 13 14 BB therapy has shown an association with reduced mortality in patients suffering from sepsis. 24 A systematic review by Tan et al , including nine studies with a total of 56 414 patients, investigated the effect of β-blockade on sepsis. The results of this systematic review suggest that BB therapy, prior to developing full-blown sepsis, is associated with significantly reduced mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 14 BB therapy has shown an association with reduced mortality in patients suffering from sepsis. 24 A systematic review by Tan et al , including nine studies with a total of 56 414 patients, investigated the effect of β-blockade on sepsis. The results of this systematic review suggest that BB therapy, prior to developing full-blown sepsis, is associated with significantly reduced mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this systematic review suggest that BB therapy, prior to developing full-blown sepsis, is associated with significantly reduced mortality. 24 Both in vivo and in vitro studies have shown that β-blockade downregulates the degree of circulating proinflammatory factors IL-6 and TNF-α, which could explain the drug’s beneficial use in acting as an inflammatory balancing agent. 12 13 25 …”
Section: Discussionmentioning
confidence: 99%
“…septic shock. [52,53] I suggest that norepinephrine should not be used in the treatment of COVID-19 patients with septic shock, instead beta-adrenergic blockers should be used.…”
Section: Why Norepinephrine Given For Septic Shock Complication In Comentioning
confidence: 99%
“…It is known that COVID-19 patients exhibit pneumonia, and severe cases had complications like acute respiratory distress syndrome (ARDS), respiratory failure and septic shock which carries a high mortality rate [2]. Recent studies showed that beta-adrenergic blockers reduced the mortality in septic shock patients [3]. Beta-adrenergic blockers also showed beneficial effects in ARDS and respiratory failure patients [4,5].…”
mentioning
confidence: 99%